Pseudomonas aeruginosa Activates PKC-Alpha to Invade Middle Ear Epithelial Cells - Mittal, Rahul; Grati, M’hamed; Yan, Denise; Liu, Xue Z. (Frontiers in Microbiology, 2016)
Otitis media (OM) is a group of complex inflammatory disorders affecting the middle ear which can be acute or chronic. Chronic suppurative otitis media (CSOM) is a form of chronic OM characterized by tympanic membrane perforation and discharge. Despite the significant impact of CSOM on human population, it is still an understudied and unexplored research area. CSOM is a leading cause of hearing loss and life-threatening central nervous system complications. Bacterial exposure especially Pseudomonas aeruginosa is the most common cause of CSOM. Our previous studies have demonstrated that P. aeruginosa invades human middle ear epithelial cells (HMEECs). However, molecular mechanisms leading to bacterial invasion of HMEECs are not known. The aim of this study is to characterize the role of PKC pathway in the ability of P. aeruginosa to colonize HMEECs. We observed that otopathogenic P. aeruginosa activates the PKC pathway, specifically phosphorylation of PKC-alpha (PKC-α) as compared to other isoforms for which bacterial OprF expression is required. This activation of PKC-α was associated with actin condensation. Blocking the PKC pathway attenuated the ability of bacteria to invade HMEECs and subsequent actin condensation. This study, for the first time, demonstrates that the host PKC-α pathway is involved in invasion of HMECCs by P. aeruginosa and subsequently to cause OM. Characterizing the role of the host signaling pathway in the pathogenesis of CSOM will provide novel avenues to design effective treatment modalities against the disease.